2009
DOI: 10.1002/ijc.24442
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer risk associated with smoking and alcohol consumption is modified by genetic polymorphisms in ERCC5, ERCC6 and RAD23B but not by polymorphisms in five other nucleotide excision repair genes

Abstract: Laryngeal cancer is known to be associated with smoking and high alcohol consumption. Nucleotide excision repair (NER) plays a key role in repairing DNA damage induced by these exposures and might affect laryngeal cancer susceptibility. In a populationbased case-control study including 248 cases and 647 controls, the association of laryngeal cancer with 14 single nucleotide polymorphisms (SNPs) in 8 NER genes (XPC, XPA, ERCC1, ERCC2, ERCC4, ERCC5, ERCC6 and RAD23B) was analyzed with respect to smoking and alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 48 publications
4
92
2
1
Order By: Relevance
“…There have been several studies showing associations between this SNP and risk of multiple cancers, including HNC, but the results from different populations were confusing rather than conclusive (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Recently, a meta-analysis with a total of 12 studies claimed that the XPD Lys751Gln polymorphism was not associated with HNC risk (17); however, no genotyping data from the Chinese population was included, with the exception of a Taiwan study with a small sample size of 154 cases and 105 controls (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies showing associations between this SNP and risk of multiple cancers, including HNC, but the results from different populations were confusing rather than conclusive (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Recently, a meta-analysis with a total of 12 studies claimed that the XPD Lys751Gln polymorphism was not associated with HNC risk (17); however, no genotyping data from the Chinese population was included, with the exception of a Taiwan study with a small sample size of 154 cases and 105 controls (30).…”
Section: Discussionmentioning
confidence: 99%
“…The His1104Asp polymorphism (rs17655), located in exon 15 of XPG, has been largely investigated in studies on susceptibility to cancers of the breast (44), lung (45), stomach (46), bladder (47), colorectum (48) and head and neck (18,36,49,50). Although it was reported that the His1104Asp polymorphism of XPG together with SNPs of several other NER genes jointly contributed to the variability of DRC (16), we found that the His1104Asp polymorphism was not associated with the risk of HNC in China, supporting the results from other published studies for this SNP and HNC risk (18,36,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ERCC6 showed a decreased risk, while ERCC5 and RAD23B increased it. 24 Furthermore, XPD and ERCC1 may be associated to poor disease free survival (DFS) in SCCHN, suggesting a significant role of NER in these tumors. 25 …”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…Four publications were excluded because of meta-analysis, control group had cancer patients or not published in English. Finally, 26 full-text articles with eligibility were included in this meta-analysis (Smith et al, 2003;Huang et al, 2006;Mechanic et al, 2006;Moreno et al, 2006;Crew et al, 2007;Jorgensen et al, 2007;Chang et al, 2008;Hung et al, 2008;McWilliams et al, 2008;Rajaraman et al, 2008;Abbasi et al, 2009;Han et al, 2009;Joshi et al, 2009;Agalliu et al, 2010;Rajaraman et al, 2010;Doherty et al, 2011;Krupa et al, 2011;Smith et al, 2011;Gil et al, 2012;Yu et al, 2012;Cheng et al, 2013;Santos et al, 2013;Wang et al, 2013;Wyss et al, 2013;Kohlhase et al, 2014;Steck et al, 2014). The flow chart which reflected the details of article selection was presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%